2001
DOI: 10.1080/09602010143000059
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer rehabilitation by students: Interventions and outcomes

Abstract: This article advocates proactive Alzheimer treatment, describes rehab interventions implemented by students, and reports positive first year outcomes for 11 mild to moderate Alzheimer's disease (AD) patients who experienced these interventions in a longitudinal Alzheimer rehabilitation research programme. Students supervised physical fitness training and volunteer work sessions for all participants and administered specific memory and language stimulation exercises to 7 of them (experimental group). Outcomes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
7

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 68 publications
1
42
0
7
Order By: Relevance
“…First year outcomes on all of the standardized tests have been reported elsewhere (Arkin, 2001). Baseline and four annual MMSE and ABCD scores (Arkin, in press).…”
Section: Standardized Test Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…First year outcomes on all of the standardized tests have been reported elsewhere (Arkin, 2001). Baseline and four annual MMSE and ABCD scores (Arkin, in press).…”
Section: Standardized Test Resultsmentioning
confidence: 99%
“…Sessions alternated between supervised volunteer service at community agencies and cultural or recreational activities (Arkin, 2001). Students were instructed to incorporate 20 min of walking into the community activity sessions, to bring the frequency of aerobic activity to the usually recommended three times per week.…”
Section: Community Activity Sessionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four of the five within-subjects exercise studies showed a positive effect on mood (Arkin, 1999(Arkin, , 2001(Arkin, , 2003Heyn, 2003). In the fifth study (Rolland et al, 2000) the exercise intervention was implemented by caregivers and led to a decrease of behavioural problems, but families themselves reported no reduction on their perceived burden.…”
Section: Effects Of Physical Activity On Affective Behaviourmentioning
confidence: 99%
“…We selected tasks and techniques where there was published evidence of memory improvement in brain injury. In short, we included training and practice in the following domains: exercises to improve motivation [32], attention [33], working memory [34], autobiographical and episodic memory [35,36,37,38] semantic memory [39] and implicit memory [40]. An adapted motivational interview was constructed for the start of the sessions [32] (that included a set of open questions regarding the actual interest of the participants in taking part in the study, expectations about possible gains to be obtained in the study, and also questions regarding the prior existence of self-initiated activities to stimulate the brain -such as crosswords, Sudoku, reading, etc.)…”
Section: Cognitive Training Interventionsmentioning
confidence: 99%